2022
DOI: 10.1111/ajad.13324
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of optimism among patients in substance use disorder inpatient treatment

Abstract: Background and Objectives Early recovery from substance use disorder (SUD) is often characterized by hopelessness and despair about the future. Optimism, or the expectation that good things will happen, may provide a buffer against despair, and motivate adaptive goal engagement and coping. Study objectives were to (1) compare levels of optimism among individuals in substance use disorder inpatient treatment to other populations and (2) examine correlates of optimism. Methods This exploratory study utilized a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Unlike the literature surrounding ARN, the optimism literature is abundant, and my research demonstrates that akin previous findings (Provost, 2022), optimism is a beneficial resource in recovery. Across three studies, I assessed optimism about recovery as an opposing force to ARN and found that optimism moderates the ambivalence increasing effects of ARN.…”
Section: Implications Applications and Future Researchsupporting
confidence: 55%
See 2 more Smart Citations
“…Unlike the literature surrounding ARN, the optimism literature is abundant, and my research demonstrates that akin previous findings (Provost, 2022), optimism is a beneficial resource in recovery. Across three studies, I assessed optimism about recovery as an opposing force to ARN and found that optimism moderates the ambivalence increasing effects of ARN.…”
Section: Implications Applications and Future Researchsupporting
confidence: 55%
“…I also examined whether this nostalgia-induced ambivalence would be heightened among those who are high (relative to low) in optimism (i.e., a positive emotion that encourages people to be hopeful about the future; Scheier et al, 1994) about their recovery. Specifically, despite optimism being a known facilitator of recovery (Provost et al, 2022), when experienced in tandem with ARN, people in recovery should feel even greater uncertainty about their recovery. I tested these novel ideas across three studies (two correlational and one prospective) and two addictive behaviours (gambling and alcohol use).…”
Section: Should I Stay or Should I Go? Ambivalence And The Opposing F...mentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, these findings are in keeping with previous studies on the low quality of life of individuals with substance use problems ( 22 , 23 ). Especially at the beginning of their clinical admission, addiction patients often experience a negative state that is characterized by abstinence-related physical symptoms and associated feelings of depression and hopelessness ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high levels of cravings during treatment, despite adequate medical management, can result in patients leaving programs prematurely against medical advice 8,12 . Conversely, Provost et al found that patients who experienced lower rates of anxiety and higher levels of optimism during inpatient treatment for SUD were more likely to continue to further levels of treatment 13 . There is a vital need for additional therapies to reduce negative affect and enhance retention for individuals with OUD during their initial stages of treatment to improve engagement in MOUD and subsequent care to reduce the risk of overdose and death.…”
Section: Introductionmentioning
confidence: 99%